An Exploratory Inquiry into the Second Language Acquisition of Junior High School Non-Readers - Palma, Angelo John C.; Madrigal, Dennis V. (Technium Social Sciences Journal, 2021)
Learning a second language bridges the gap and links people to the world by creating a mellifluous relationship where information, ideas, and culture are shared through communication. The Philippines is ranked fifth in the world’s largest English speaking countries. However, surveys on International academic assessment for high school students found that the country ranks lowest in English Language reading and speaking comprehension. This paper explores the experiences of junior high school non-readers in a public high school on second language acquisition in Negros Occidental, Philippines. This qualitative research utilized a phenomenological approach. The Philippine Informal Reading Inventory Assessment results were utilized as part of the inclusion criteria to identify the participants. The data were gathered through an in-depth interview and were analyzed using the thematic analysis approach by Lichtman (2010). This undertaking generated three themes that depict the lived experiences of the respondents in L2 acquisition: (a) Language Origin, (b) Practice of Target Language, (c) Learning Conditions. The findings indicate that external and internal factors substantially affect the L2 learning of students, and these factors in SLA will remain incessant when not addressed at once.